Influence of Light Wavelength on the Growth Performance and Protein Content of Arthrospira platensis - Gabriela Sabatin Siama; Marvel Reuben Suwitono; Doli Situmeang (Jurnal Biologi Tropis, 2026)
Microalgae play an important role in aquatic ecosystems as primary producers and have significant potential as a sustainable source of protein. One of the microalgae with high economic value is Arthrospira platensis, which is rich in bioactive compounds and protein content. Light is a key factor influencing microalgae growth, particularly its wavelength and spectrum, which can affect biomass production and biochemical composition. This study aimed to analyze the effect of different LED light wavelengths (red, blue, and a combination of red–blue) on the growth performance and protein content of Arthrospira platensis. The experiment was conducted in January 2026 using a completely randomized design with three treatments and three replications. The microalgae were cultivated in Walne medium under controlled conditions with continuous aeration for 14 days. Growth was monitored daily, and protein content was analyzed using a UV-Vis spectrophotometer at wavelengths of 280 nm and 260 nm. The results indicated that different light wavelengths significantly influenced the growth and protein content of Arthrospira platensis. The combination of red–blue light showed better performance compared to single wavelengths in enhancing biomass production and protein content. In conclusion, the use of combined LED light spectra can optimize the cultivation of Arthrospira platensis and improve its potential as an alternative protein source